1971
DOI: 10.1111/j.1476-5381.1971.tb08036.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (±) dihydroxy ephedrine and (±) dihydroxy pseudoephedrine on adrenergic transmission in mesenteric arteries

Abstract: Summary1. The effect of (±) dihydroxy ephedrine (DHE), (±) dihydroxy pseudoephedrine (DHPE) and isoprenaline on the vasoconstrictor responses of the perfused mesenteric arteries of the rat produced by stimulation of their periarterial sympathetic fibres, and in the responses to injected noradrenaline, has been studied. 2. DHE and DHPE inhibited the responses to nerve stimulation and increased the responses to injected noradrenaline. 3. Isoprenaline slightly decreased the basal perfusion pressure and reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Using perfused rat mesenteric arteries, Malik demonstrated that although ME inhibit-ed responses to nerve stimulation, it did not inhibit the effect of NE infusion. 22 In order to study ME further, it was necessary to consider the implications of its two asymmetric carbon atoms, which yield four isomeric forms. Erythro-ME already had been separated from threo-ME by earlier investigators who noted that the former was considerably more active.…”
mentioning
confidence: 99%
“…Using perfused rat mesenteric arteries, Malik demonstrated that although ME inhibit-ed responses to nerve stimulation, it did not inhibit the effect of NE infusion. 22 In order to study ME further, it was necessary to consider the implications of its two asymmetric carbon atoms, which yield four isomeric forms. Erythro-ME already had been separated from threo-ME by earlier investigators who noted that the former was considerably more active.…”
mentioning
confidence: 99%